Characteristics of stress fractures in young athletes under 20 years - Ohta-Fukushima, M.; Mutoh, Y.; Takasugi, S.; Iwata, H.; Ishii, S. (The Journal of Sports Medicine and Physical Fitness, 2002)
BACKGROUND: With the popularization of organized sports among adolescents and children, the clinical cases of stress fractures in young athletes have increased. This study was carried out to investigate the characteristics of stress fractures in young athletes. METHODS: During the 18-month period between January 1996 and June 1997, new clinical cases of stress fracture due to sports activities were collected from 39 hospitals in Japan. RESULTS: We analyzed 222 stress fractures in 208 athletes under 20 years of age (108 males: 14.4+/-2.2 years, 100 females: 15.2+/-1.5 years). Among these cases, the peak age of occurrence was 16. The most common sport causing stress fracture was basketball. The tibia was the most common location. About 70% of the patients participated in the respective sport for 6 or 7 days per week. High school students trained significantly more often than the primary and junior high school students (p<0.0001). There was a statistically significant difference in the return time to the sport between the cases who visited a hospital within 3 weeks and those who waited for more than 3 weeks after the onset of symptoms (return time, 10.4 vs 18.4 wks). Several cases visited a hospital beyond 8 weeks after the onset of symptoms regardless of the continuous pain of stress fracture, and their recovery was prolonged. CONCLUSIONS: It is important to educate young athletes that continuous pain lasting over 3 weeks is a warning signal to the body, and that early diagnosis leads to early recovery.